2021
DOI: 10.4314/rjmhs.v4i2.7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Factors Contributing to Medicine Expiry in Rwanda: Case of the Medical Procurement and Production Division

Abstract: BackgroundRegardless of the significant efforts used and put in place to enhance supply chain performance in Rwanda, there is still poor inventory management and big loss due to expiry of medicines at Medical Procurement and Production Division (MPPD).ObjectiveTo assess the factors that contributes to expiry of medicines at MPPD and formulate recommendations for the improvement of the current situation.MethodsThis is a descriptive cross-sectional study used for 25 respondents. A questionnaire containing closed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 1 publication
(1 reference statement)
1
9
0
Order By: Relevance
“…This result is higher than that of a study conducted in the West Wollega Zone, where the total value of reproductive health medicines thrown away due to expiration was 357,920.52 ETB (12,323.81 US dollars) [ 34 ], and Shoa Zone, Oromia regional state, the total monetary value of wasted medicines was 500,522.09 ETB [ 17 ]. However, it was lower than a study conducted in Ruanda, which revealed that the total value of expired products for all program categories was RWF 6,046,778,655 [ 12 ]. Pharmaceuticals that have passed their expiration dates endanger the environment as well as the healthcare system.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…This result is higher than that of a study conducted in the West Wollega Zone, where the total value of reproductive health medicines thrown away due to expiration was 357,920.52 ETB (12,323.81 US dollars) [ 34 ], and Shoa Zone, Oromia regional state, the total monetary value of wasted medicines was 500,522.09 ETB [ 17 ]. However, it was lower than a study conducted in Ruanda, which revealed that the total value of expired products for all program categories was RWF 6,046,778,655 [ 12 ]. Pharmaceuticals that have passed their expiration dates endanger the environment as well as the healthcare system.…”
Section: Discussionmentioning
confidence: 67%
“…Study conducted in Africa specially in East Africa, money lost due to expired medicines was surprising. As evidence study performed in Rwanda, a study found that the total value of expired medicines was RWF 6,046,778,655, with major contributing factors including supply chain management ranking at 90%, other factors ranking at 73%, poor storage management ranking at 68%, and excessive drug supply ranking at 67% [ 12 ]. Also, the study conducted in South Africa explored the total estimated value of financial losses due to medicine expiry was R 836 029; an estimated annual revenue loss of 0.6% of the total hospital expenditure that contributed to lack of standard treatment guideline knowledge among prescribers [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 The other contributing factors to the expiry of health commodities and wastage were a weak stock control system, and over supplying of drugs. 32 In this study, the main sources of wastage of medicines were expiry (99.3%). The perceived reasons for such medicine’s wastage were delivery of medicines with the near-expiry date (<6 months) to the health facilities by suppliers (Ms=4.23), excessive supply of nearly expired medicines, 32 , 33 poor coordination and communication with key stakeholders (suppliers, health bureau/office, NGOs‟s) (Ms=4.2) and availability of overstocked medicines caused by inappropriately forecasted needs of health facility (Ms=3.83) of South Gondar zone, Ethiopia.…”
Section: Discussionmentioning
confidence: 67%
“…Jawaher Matar Alwashahi, Mithaq Ibrahim Alqartubi and Jawaher Hamed Alhakmani. Smart Identification and Notification of Drugs in Medical Pharmacy using IoT 5 According to [4] There is a big loss of medicine in Rwanda because of less monitoring, the purpose of this research is to evaluate the factors which can occur the expired medicine. The study research was used 25 responders, they used close-ended questions and they were focusing on factors that can produce the expired data, they focus more on the pharmacist who is working in MPPD, the highest response for this research is 96% response rate.…”
Section: Literature Reviewmentioning
confidence: 99%